Insight and psychosis - Amador, Xavier Francisco; David, Anthony S. (OUP E-Books., 2004)
The insight a patient shares into their own psychosis is fundamental to their condition - it goes to the heart of what we understand 'madness' to be. Can a person be expected to accept treatment for a condition that they deny they have? Can a person be held responsible for their actions if those actions are inspired by their own unique perceptions and beliefs - beliefs that no-one else shares? The topic of insight in schizophrenia and related disorders has become a major focus of research in psychiatry and psychology. It has important clinical implications in terms of outcome, treatment adhere.